Rehabilitation coordinator intervention versus control in psychiatric specialist care for return to work and reduced sick leave: study protocol of a randomised controlled trial - Åsa Andersén; Erik Berglund; Ingrid Anderzén (BMC, 2020)
Abstract Background Mental disorders are the most common reason for sick leave in Sweden. Knowledge about effective methods to help these individuals to return to work (RTW)/entry into work or studies is limited. Rehabilitation coordinators (RC's) have been introduced within healthcare with the purpose to promote cooperation, streamline the sick leave and rehabilitation process, and facilitate RTW for sick-listed patients. The function of RC's has shown positive results by reducing sick leave within primary healthcare. However, the function has not been evaluated in terms of specialist psychiatry. This paper describes the design of a study to evaluate effects of a RC intervention on sick leave and RTW/entry in work or studies in patients with moderate to severe affective and/or moderate to severe anxiety disorders within specialist psychiatric care. Methods A randomised controlled trial (RCT) comparing an intervention group receiving support from a RC with a control group receiving treatment as usual (TAU). The target group is patients on sick leave, treated for affective and/or anxiety disorder, aged 25-64, with or without employment. Discussion This study gives the possibility to evaluate a RC intervention for individuals with mental disorders. If the study has promising vocational outcomes, it may be of importance for the participants in many ways, e.g. increase participation in society, provide economic benefits and improve health and wellbeing. This would be valuable for the individual as well as for the society. Trial registration The study is registered at the Clinicaltrials.gov Register Platform (ID NCT03729050) in 2 November 2018.